The intensive interaction handbook - Hewett, Dave; Firth, Graham; Barber, Mark; Harrison, Tandy (Los Angeles SAGE, 2012)
Intensive Interaction is a straightforward approach to teaching the fundamentals of communication to children and adults who have severe learning difficulties or autism, and who are still at an early stage of communication development. This book is a practical guide to help those wishing to implement Intensive Interaction in their setting, and it provides detailed advice and step-by-step guidance as well as a consideration of all the issues associated with carrying out this approach.
Human communication and the background to intensive interaction -- The nature of human communication / Dave Hewett -- Background to intensive interaction / Graham Firth -- How do human beings start learning to communicate? / Dave Hewett -- Practicalities of doing intensive interaction -- Preparing for intensive interaction / Dave Hewett -- Getting going / Dave Hewett -- Further and continuing progress / Dave Hewett -- Recording the activities and maintaining the processes / Mark Barber -- Supporting intensive interaction in workplaces / Graham Firth and Dave Hewett -- Doing intensive interaction at home / Tandy Harrison -- Issue, topics and community -- Some associated issues and topics / Dave Hewett -- The intensive interaction community / Graham Firth.
Includes bibliographical references (pages [153]) and index.
Keywords: Communication